ROS-generating, pH-responsive and highly tunable reduced graphene oxide-embedded microbeads showing intrinsic anticancer properties and multi-drug co-delivery capacity for combination cancer therapy - Adilakshmi Boddu; Sreekanth Reddy Obireddy; Dahong Zhang; K. S. V. Krishna Rao; Wing-Fu Lai (Drug Delivery, 2022)
The development of effective carriers enabling combination cancer therapy is of practical importance due to its potential to enhance the effectiveness of cancer treatment. However, most of the reported carriers are monofunctional in nature. The carriers that can be applied to concomitantly mediate multiple treatment modalities are highly deficient. This study fills this gap by reporting the design and fabrication of ROS-generating carbohydrate-based pH-responsive beads with intrinsic anticancer therapy and multidrug co-delivery capacity for combination cancer therapy. Sodium alginate (SA) microspheres and reduced graphene oxide (rGO)-embedded chitosan (CS) beads are developed via emulsion-templated ionic gelation for a combination therapy involving co-delivery of curcumin (CUR) and 5-fluororacil (5-FU). Drug-encapsulated microbeads are characterized by FTIR, DSC, TGA, XRD, and SEM. 5-FU and CUR-encapsulated microbeads are subjected to in vitro drug release studies at pH 6.8 and 1.2 at 37 °C. Various release kinetic parameters are evaluated. The results show that the Korsmeyer-Peppas model and non-Fickian release kinetics are best suited. The microspheres and microbeads are found to effectively act against MCF7 cells and show intrinsic anticancer capacity. These results indicate the promising performance of our beads in mediating combination drug therapy to improve the effectiveness of cancer treatment.